Teoretyczne koncepcje strategii przedsiębiorstw globalnych - Ćwik, Krzysztof (Theoretical conceptions of strategies of global enterprises, 2005)
In this article problems of activity of international enterprises have been presented. The article presents the main types of international enterprises and introduces the theoretical base of strategies and competitive moves made by global enterprises in the world market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 171-182